ANALISIS PENILAI KEWAJARAN HARGA SAHAM DENGAN METODE PRICE TO BOOK VALUE PADA PT. KROM BANK INDONESIA TBK 2022 – 2023 - Sihombing, Mariauli; Simamora, Depi Hardiati; Tesalonika, May; Miranda, Elsa; Liliana, Ola Venina; Kesia, Tiori; Hasugian, Christnova; Siallagan, Hamonangan (Komunitas Manajemen Kompetitif, 2025)
The development of investors in Indonesia has shown a significant increase to date. Therefore, the aim of this research is to provide insight for both beginners and experienced investors in investing in the capital market. By understanding proper analysis, it is hoped that they will be able to evaluate share price conditions before making a sale or purchase transaction. This is done by assessing the value of the shares, whether they are overvalued (expensive) or undervalued (cheap), using the analysis method, namely price to book value. The research method used in this study is qualitative and descriptive. Data analysis was carried out using stock valuation techniques based on the price to book value method, then the data was processed using Microsoft Office Excel. The research data source comes from secondary data taken from the Annual Report of Pt. Krom BI, and the official sites of related companies.. Assessing the fairness of share prices using the Price to Book Value (PBV) method, the results showed that the company is currently in an overvalued share condition, with a PBV value greater than 1.